The role of the openings in the out-of-plane behaviour of masonry infill walls. (1st October 2021) - Furtado, André; Arêde, António; Rodrigues, Hugo; Varum, Humberto
Highlights: Experimental study on the effect of the openings in the out-of-plane behavior of infills in RC buildings. Full-scale tests of horizontal hollow clay bricks, with a central window and the remaining one with a central door. The openings reduced the maximum strength of 30% for undamaged panels, and it occurred for lower displacement demands. The increase of the opening area did not affect the peak load but reduces the energy dissipation capacity. Abstract: This research work aims to present an experimental study concerning the effect of the openings in the out-of-plane (OOP) behaviour of masonry infills in RC buildings. The experimental campaign comprises the OOP testing of three full-scale infill walls made up of horizontal hollow clay bricks, two of them with a central window and the remaining one with a central door. One of the specimens with a central opening was first subjected to a previous in-plane test and, after that, the damaged wall was subjected to an OOP test. All the tests consisted of applying a loading–unloading-reloading history of imposed displacements in the OOP direction through a uniformly distributed load. An innovative setup was used and adapted for each wall typology. The results are presented in terms of OOP force–displacement responses, damage evolution, relative stiffness and energy dissipation capacity. Finally, the test results are compared to each other to assess the effect of: i) the area of the opening; and ii) the previous damage. It was found that the openings reduced the maximum strength of 30% for undamaged panels, and it occurred for lower displacement demands. The increase of the opening area did not affect the peak load; however, it reduced their energy dissipation capacity significantly. The energy dissipation capacity reduced from 42% to 70%.